Reassembly of protein-lipid complexes into large bilayer vesicles: Perspectives for membrane reconstitution - Darszon, A. (1980)
Protein-lipid complexes in apolar solvents reassemble into large bilayer protein-lipid vesicles (PLVs) with diameters of several micrometers. PLVs form spontaneously upon hydration of the protein-lipid complex residue after solvent removal. This procedure has been applied to the following membrane proteins: bovine and squid rhodopsin, reaction centers from Rhodopseudomonas sphaeroides, beef heart cytochrome c oxidase, and acetylcholine receptors from Torpedo californica. PLVs have a large internal aqueous space (e.g., 790 μl/mg of lipid for cattle rhodopsin vesicles). Freeze-fracture replicas of PLVs revealed that both internal and external leaflets contained numerous intramembranous particles with diameters between 80 and 120 Å, depending on the specific protein incorporated in the membrane. The optical spectral properties of rhodopsin and reaction centers in PLVs were similar to those recorded in the respective natural membrane. Furthermore, bovine rhodopsin in PLVs was chemically regenerable with 9-cis-retinal. Actinic illumination induced proton efflux from reaction center vesicles that was abolished by proton ionophores. Therefore, this method is suitable for the incorporation of some membrane proteins in their functional state. PLVs were penetrated with microelectrodes and visualized by the injection of a fluorescent dye. Preliminary electrical recordings were obtained by sealing PLVs to a hole in a septum separating two aqueous compartments. These studies suggest that PLVs assembled by this procedure permit the simultaneous analysis of reconstituted membranes by chemical, optical, and electrical techniques.